User perceptions of mental health consequences of hallucinogen use in self-identified spiritual contexts - Johnstad Petter Grahl (Nordic Studies on Alcohol and Drugs, 2015)
AIMS – The article aims to gain insight into the private worlds of users of hallucinogenic drugs in spiritual contexts, with a focus on the self-perceived mental health implications of their practices. This will help us understand the rationale behind and consequences of hallucinogenic drug use.